The Impact of CRM on Innovation Capabilities: A Study on Industries of Pakistan - Ahmed, Farhan; Siddiqui, Danish Ahmed (American Journal of Trade and Policy, 2019)
The purpose of this research is to determine the impact of CRM on innovative capabilities where the comparative study has been conducted between the services and manufacturing industries in Pakistan. For this purpose, the factors affecting CRM include information sharing, customer involvement, long-term partnership, joint problem solving, and technology based CRM while for measuring the innovative capabilities, product innovation, process innovation, and service innovation has been used. The data collected from 60 employees working in different service and manufacturing firms in Karachi. The results show that there is a significant impact on customer involvement, joint problem solving and technology based CRM on innovation capabilities of firms. It is suggested to refrain from customer involvement because it is observed that involving the customers negatively influences the innovation capabilities of manufacturing industry and thus, it has been recommended for companies to abstain from drawing in customers. The research also suggests adding supplier integration to form more effective innovations programs.